2020
DOI: 10.1155/2020/6501294
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Kinetic Behaviour of Pseudoalteromonas espejiana Assisted Biosynthesized Gold Nanoparticles

Abstract: Pseudoalteromonas espejiana (P. espejiana) is a marine bacterium known for its high resistance to alkalinity. The ability of P. espejiana to reduce Au (III) and biosynthesize gold nanoparticles (AuNPs) is found positive and was confirmed using UV-VIS, EDS, SEM, and TEM studies. Previously, many studies have been reported regarding the crystalline nature of AuNPs; therefore, this research aims at studying the crystal growth behaviour of AuNPs through DLS and TEM studies. Spherically shaped and monodispersed, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, Gupta et al . 32 observed that with increasing of time, the AuNPs agglomerate and fuse to develop into larger crystals, and thus large-sized AuNPs are produced.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Gupta et al . 32 observed that with increasing of time, the AuNPs agglomerate and fuse to develop into larger crystals, and thus large-sized AuNPs are produced.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the induced resistance was mediated by copper oxidase CopA, which was reduced to Au(0) nanoparticles in the periplasm by the intermediate detoxification Au complex. , This is a biological way for bacteria to detoxify metal ions and an unnatural process of biomineralization. Second, there are studies on the complex structure of biosynthetic DNA–gold in Escherichia coli and Staphylococcus, which has fluorescence effect and is used for the bioresponsive fluorescence imaging of bacteria. , Different bacteria were used to explore the biosynthesis of gold nanoparticles, revealing that different bacterial biosynthetic pathways are inconsistent, leading to differences in efficiency and gold nanostructures. …”
Section: Biosynthesis Systemsmentioning
confidence: 99%